Studies on alkaline solid polymer blends electrolyte for batteries / Faizatul Farah Hatta - Hatta, Faizatul Farah (2006)
Alkaline solid polymer blends electrolyte (ASPBE) films comprising a blend of poly(vinylalcohol) (PVA) and poly(vinylpyrrolidone) (PVP), potassium hydroxide (KOH) as ionic dopant, ethylene carbonate (EC) and propylene carbonate (PC) as plasticizer have been prepared by solution casting technique. The concentration ratio of the polymer blend, ionic dopant and plasticizer was varied systematically. The PVAPVP blend has good mechanical strength as tested using tensile measurement. X-ray diffraction (XRD) studies have been conducted to investigate the complexation in the alkaline solid polymer blends electrolyte. The XRD results revealed that the amorphous domain of PVA was increased when the PVP was blended. The variation in film morphology was examined by scanning electron microscopic (SEM). The thermal properties of these films were performed using differential scanning calorimeter (DSC) and the result has confirmed the miscibility between the polymeric components. The conductivity was studied using complex impedance spectroscopy to investigate ionic conduction in blending PVA/PVP, PVA/PVP-KOH, PVA/PVP-KOH-EC and PVA/PVP-KOH-PC electrolyte systems. The complex impedance spectroscopy results revealed that the high-frequency semicircle was due to the bulk effect of the material. The conductivity was found to increase in the order of 10"7 -10"4 Scm"1 with the increase in ionic dopant and plasticizer concentrations at temperature range from 30-110 °C. The PVA/PVP system with a composition of 80 wt.% PVA and 20 wt.% PVP exhibited the highest conductivity of (2.2 ± 1.4) x 10"7 Scm"1 and the value was enhanced to (1.5 ± 1.1) x 10"4 Scm"1 when 40 wt.% KOH was added.